#### Answer

$y' = -cosecx(cosec^{2}x +cot^{2}x)$

#### Work Step by Step

$y = \frac{cosx}{sin^{2}x}$
$y = cotx\ cosecx$
$y' = -cosec^{2}x\ cosecx - cotx\ (cosecx\ cotx)$
$y' = -cosec^{3}x- cot^{2}{x}\ cosecx$
$y' = -cosecx(cosec^{2}x +cot^{2}x)$

Published by
Pearson

ISBN 10:
0321999584

ISBN 13:
978-0-32199-958-0

$y' = -cosecx(cosec^{2}x +cot^{2}x)$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.